Experimental and modeling study of the autoignition characteristics of gasoline/hydrogenated catalytic biodiesel blends over low-to-intermediate temperature. (1st April 2022) - Zhong, Wenjun; Yuan, Qifei; Liao, Jingjing; Mahmoud, Nasreldin.M.; Yuan, Wenhua; He, Zhixia; Wang, Qian; Yu, Liang; Lu, Xingcai
Highlights: The auto-ignition characteristics are studied for gasoline/HCB blends. The blending ratio affects the TIDTs by the FIDTs. A detailed mechanism is applied to successfully predict the trend of the auto-ignition of blends. The dominating reactions are identified to account for the variation of ignition delay time. Abstract: Gasoline/Hydrogenated catalytic biodiesel blending fuel is a prospective alternative fuel for gasoline compression ignition (GCI) engine which has the potential to solve the ignition difficulties of GCI especially at low load conditions. However, the autoignition behavior of gasoline/hydrogenated catalytic biodiesel blends is unknown. In this study, the ignition delay times of gasoline/hydrogenated catalytic biodiesel (HCB) blends were measured in a heated rapid compression machine over a wide range of conditions (the temperature range of 655–870 K, pressures of 10 and 15 bar, equivalence ratios of 0.5–1.5). Experimental results show that the measured ignition delay time of the gasoline/HCB blends exhibits negative-temperature coefficient behaviors under the investigated conditions. The total ignition delay times diminish with rising pressure, equivalence ratio and HCB ratio in the blends. The simulation results of ignition delay times for gasoline/HCB blends using a detailed mechanism are compared with experimental data. The detailed model can predict the trends of ignition delay time well during low-to-intermediate temperature region. Finally, kinetic analyses were performed under different compressed pressure, temperature, equivalence ratios and blending ratios. The dominating reactions and decisive factors of ignition are explored to gain a deeper understanding of the ignition characteristic of gasoline/HCB blends. It is found that the autoignition of fuel is completely caused by HCB related reactions at low temperature, which explains why the blending of HCB can expand the working condition downward from the perspective of chemical kinetic.